O09.4 Mobilization For HIV, Syphilis and Hepatitis B and C Testing During Brazil's Carnival. (13th July 2013) - Bolzan, A; Santos, E; Serafim, D; Ayer, E; Neto, A; Chaves, M; Araújo, V; Cerqueira, J
Abstract : Introduction: Testing campaigns (entitled "Get to know") during high-traffic public events have been conducted in Brazil since July 2008. On these occasions, people are offered information about health and prevention and rapid tests (RTs), as well as condoms and lubricating gels. Initially, only rapid HIV testing was conducted; RTs for syphilis screening was included in 2010 and hepatitis B and C screening in 2012. Twenty-two national mobilizations were organised between 2008 and 2012, with approximately 26, 300 RTs performed. Methodology: A large number of people attend the carnival celebrations in the cities of Recife and Salvador and are the focus of Ministry of Health campaigns. In 2013, for the first time, the "Get to Know" campaign in these cities offered RTs for HIV, syphilis, and hepatitis B and C. Testing was conducted in health centres near places where large numbers of people congregated and at temporary centres at the carnival venues. In cases with RT reactive results, patients received the test results and were referred to qualified services for follow-up and healthcare. Results: More than 8, 000 tests were performed during the four days of carnival in Recife and Salvador. In Salvador, 5, 280 tests were conducted in three locations, and 1, 458, 984 condoms were distributed by eleven mobile teams. Of those tested, 16 were reactive for HIV, 84 for syphilis, 7 for hepatitis B, and 14 for hepatitis C. In Recife, 5, 527 RTs were performed in 3 locations, and 800, 000 condoms were distributed. Twenty people were reactive for HIV, 60 for syphilis, 2 for hepatitis B, and 4 for hepatitis C. Conclusion: The "Get to Know" campaign has been proven efficient in scaling up access to early diagnosis and reaching large numbers of people with information about the importance of getting tested and with awareness-raising activities about prevention.